The Implementation of Wordwall Application in Teaching Reading for General Communication in Higher Education - Inayah, Ratih; Hartono, Rudi; Wahyuni, Sri (PROJECT (Professional Journal of English Education), 2025)
This study investigates the implementation of the Wordwall application as a digital learning tool to support reading skills development for general communication among first-year undergraduate students in the English Education Department. Employing a qualitative research approach, the study involved 30 students participating in classroom activities using the Word Wall in a natural learning environment. Data were collected through direct classroom observations, semi-structured interviews, and students’ reflective journals to capture their experiences and perceptions regarding the use of the application. The findings indicate that the Word Wall application effectively enhances student engagement by creating an interactive and visually appealing learning atmosphere. This increased engagement contributed to higher motivation levels and encouraged active participation during reading exercises. Furthermore, students demonstrated improved vocabulary acquisition and reading comprehension as a result of the repeated and contextualized exposure to words facilitated by the Wordwall activities. Although some students faced initial challenges such as limited digital literacy and occasional technical issues, they adapted quickly, which suggests that the integration of such digital tools is feasible and beneficial in higher education contexts. The study also highlights the potential of technology-enhanced learning to address common difficulties in teaching reading for general communication by providing dynamic and accessible vocabulary practice.